Using light stable isotopes to assess stream food web ecology in a general ecology laboratory course. Issue 5 (20th October 2021) - Carroll, Hannah M.; Houston, Derek D.; Ankerstjerne, Suzanne; Wanamaker, Alan D.
ABSTRACT: Stable isotopes in natural materials provide a powerful way to study energy flow in many systems and are widely used in fields such as archaeology, ecology, forensics, geochemistry, geology, oceanography, palaeoecology and palaeoclimatology. Based on the manner in which stable isotopes fractionate in natural systems, they allow scientists to address a wide array of research topics ranging from tracking climatic shifts, ascertaining organisms' migratory patterns, matching organisms to their diets and/or environments, assessing food web bioenergetics, documenting ecosystem changes through time, measuring soil carbon budgets and soil microbial activity, etc. Hence, it may be a viable option to use stable isotopes to investigate stream and food web ecology with students. Students with no prior experience working with stable isotopes successfully met learning objectives by completing the requisite field and laboratory protocols, analysing data, interpreting results, and communicating their findings in a report modelled after a peer-reviewed scientific journal article. While this activity focused on food web ecology in a stream ecosystem, the method is repeatable, cost-effective, and can be modified relatively easily to evaluate food webs in virtually any other ecosystem.